THE DARK SIDES OF WORKSTATION: ERGONOMICS ASPECTS AND OCCUPATIONAL DISEASES TOWARDS JOB PERFORMANCE AT GENERAL HOSPITAL IN MALAYSIA (Journal of Engineering and Health Sciences, 2020)
The purpose of this study is to identify the ergonomic aspects in the workplace and examining the occupational diseases due to ergonomics issues. This study provide the analysis of the ergonomic aspects and occupational diseases towards job performance nurses in general hospitals in Malaysia. In order to conduct this study, the researchers will collect the data from primary and secondary data. The survey will be stratified from peoples who are working at hospital specifically, nurses.  The expected outcomes and implication of this study is the development of employees’ health and wellbeing in which basically it is in line with the government's commitment of "1Care for 1Malaysia", that was implemented under the Economic Transformation Program (ETP) and to respond Industrial Revolution 4.0. Due to the increasing cases of Musculoskeletal Disorders (MSDs) and job stress among employees, especially among nurses, a study of the ergonomic aspects and occupational diseases towards job performance is crucial.